Spasmolytic effect of Acmella oleracea flowers extract on isolated rat ileum - Acharaporn Duangjai; Wichuda Phiphitphibunsuk; Niphaphon Klomkiao; Plangkul Rodjanaudomwuttikul; Praewanit Ruangpoom; Sudarat Autthakitmongkol; Acharaporn Ontawong; Nattakorn Kamkaew; Maleeruk Utsinthong; Surasak SaoKaew (Shahrekord University of Medical Sciences, 2021)
Introduction: Acmella oleracea has been used as a traditional medicine for the treatment of asthma, sore throat, haemorrhoids and toothache. However, whether A. oleracea has gastrointestinal functions, such as regulation of intestinal contractions, has not been fully elucidated. Therefore, the aim of the present study was to investigate the effect of A. oleracea flowers extract (AFE) on rat ileum contractions and the possible mechanism(s) of its action. Methods: The extract was prepared using the Soxhlet apparatus with 95% ethanol. Ileum was removed from male Wistar rats and mounted in an organ bath containing Krebs solution. The tissue contractions were recorded by an isotonic transducer under 1 g tension. Results: The cumulative concentrations of the AFE (0.01-1 mg/mL) reduced the ileum contractions induced by KCl (80 mM) (n = 6, P < 0.05). AFE (1 mg/mL) attenuated the contractions induced by cumulative concentrations of CaCl2 (1-20 mM), while the spasmolytic effects of the extract were not reduced after tissue incubation with N (ω)-nitro-L-arginine methyl ester (L-NAME) (100 μM, 20 minutes). Conclusion: These results suggest that AFE inhibits ileum contractions without involving the nitric oxide pathway, which is possibly mediated via blockade of voltage-dependent calcium channels. A. oleracea may be useful in gastrointestinal disorders such as diarrhoea.